Performance appraisal for green/environmental friendliness of a supply chain department - Solomon Olasunkanmi Odeyale (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This paper aims at proposing a method for evaluating the environmental friendliness of a supply chain department in any organization. Supply chain involves activities that could affect the natural environment and if these activities are not properly evaluated and monitored, it could affect the natural environment and also generate ecological performance change. Design/methodology/approach: The model for the appraisal consists of 5 criteria and 30 subcriteria. The method is applied at 3 level; beginning with finding the relative weight of the subcriteria under each criterion using Analytic Hierarchy Process (AHP), followed by computing the value associated with each level descriptor in a scale. Some subcriteria have 5 level descriptors (very strong/moderate /weak/very weak / no), some subcriteria have 3 level descriptors (always / sometimes/ never) and some have 2 levels descriptor (yes/no). Finally the method is concluded by the means of an additive model, whereby the weight associated with each subcriteria is multiplied by the corresponding level descriptor and summed up to get the limit/state. This methodology is called the weighing multiplication and additive model (WMAAM). Finding: Supply chain (SC) involves operational activities and for these activities to be environmental friendly, they have been categorized under criteria namely; green design, green procurement, green manufacturing, environmental management and green marketing. These criteria which consist of 30 subcriteria are evaluated in other to compute the overall environmental friendly appraisal of the SC department. Practical Implication: The study plays important role in understanding various areas to be monitored and considered during supply chain activities in order to achieve a green supply chain management or an environmental friendly supply chain. Originality/value: The main contribution of this work is to propose an effective methodology that guides SC practitioners on carrying out green performance appraisal of a SC department in any organization.
Keywords: 650; Analytic hierarchy process (AHP); environmental management; green supply chain management; performance appraisal